Green synthesis of silver and palladium nanocomposites: a study of catalytic activity towards etherification reaction. Issue 8 (2nd November 2020) - Singh, Pritam; Halder, Mita; Ray, Santanu; Bose, Adity; Sen, Kamalika
Abstract : This work deals with the synthesis of biomolecule-based monometallic Ag and Pd and bimetallic Ag–Pd nanocomposites and their catalytic activity towards etherification reaction. Abstract : This work deals with the synthesis of biomolecule-based monometallic Ag and Pd and bimetallic Ag–Pd nanocomposites and their catalytic activity towards etherification reaction. The as-synthesized nanocomposites were characterized using N2 adsorption–desorption, high-resolution transmission electron microscopy, Fourier transform infrared spectroscopy, absorption spectroscopy, thermogravimetric analysis, powder X-ray diffraction analysis, X-ray photoelectron spectroscopy and inductively coupled plasma optical emission spectrometry. All three types of nanocatalysts are based on the formation of a complex between the metal and a biomolecule, rutin, with association constant ( K a ) values of 3833.33 M −1, 606.48 M −1 and 492.36 M −1 for monometallic Ag and Pd and bimetallic AgPd systems, respectively. The nanocomposites showed catalytic activity towards etherification reactions between different substituted cinnamyl acetate and phenolic compounds under mild and eco-friendly conditions. The values of the product yields were 85–91% with turnover frequency in the range of 17 490–18 724 h −1 . The best catalyst was shown to be reusable for 4 cycles without considerable loss in the product yield. The catalytic activity of the Ag-based heterogeneous catalyst towards such O -allylation reaction of phenolic compounds is quite interesting. However, to the best of our knowledge, the literature reports based on such reactions using Ag-based heterogeneous catalysts are still lacking.